2017
DOI: 10.1093/jamia/ocx115
|View full text |Cite
|
Sign up to set email alerts
|

Medication-related clinical decision support alert overrides in inpatients

Abstract: Almost three-quarters of alerts were overridden, and 40% of the overrides were not appropriate. Future research should optimize alert types and frequencies to increase their clinical relevance, reducing alert fatigue so that important alerts are not inappropriately overridden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 45 publications
2
105
2
6
Order By: Relevance
“…Alert fatigue can negate the potential patient safety benefits of interruptive CDS, and it is a widely discussed concern. 3, 4,7,9,10,14,21,22 Previous research has reported effective techniques for categorizing historical interruptive DDI alert data for critical review, organizing at the drug or drug category level, and calculating frequencies of alert occurrence. [11][12][13][14][15][16] Interdisciplinary panels can review an institution's alert data and safely identify alerts to deactivate or modify.…”
Section: Discussionmentioning
confidence: 99%
“…Alert fatigue can negate the potential patient safety benefits of interruptive CDS, and it is a widely discussed concern. 3, 4,7,9,10,14,21,22 Previous research has reported effective techniques for categorizing historical interruptive DDI alert data for critical review, organizing at the drug or drug category level, and calculating frequencies of alert occurrence. [11][12][13][14][15][16] Interdisciplinary panels can review an institution's alert data and safely identify alerts to deactivate or modify.…”
Section: Discussionmentioning
confidence: 99%
“…Our study particularly challenges the usefulness of automated notifications about potassiumincreasing DDIs despite a low alert burden. In this context, we increasingly question the justification for both (i) direct costs due to research, development and maintenance of the information technology and (ii) indirect expenses due to the burden providers experience in handling clinically insignificant notifications that are to be appropriately overridden [5,34]. Ultimately, even if potassium-increasing DDIs were to clearly increase mortality due to serious hyperkalaemic states with fatal cardiac arrhythmias, CDS could still not guarantee clinical effectiveness, which is hampered by high override rates [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite PASS having been adopted by some hospitals, the positive effects are often negligible, and the system override rate continues to remain quite high. Previous studies have documented that monitoring systems do have positive impacts on medical performance [6] and also have highlighted a high level of override rates (73.3%) in PASS contexts [5,7]. One study also presented an insignificant correlation between the system in hospitals and prescription behavior [8].…”
Section: Introduction Backgroundmentioning
confidence: 97%
“…Most hospital information systems (HISs) in China provide informative guidance in order to provide required information for decision-makers, which further aim to support their judgments and adoption of the systems [5]. As a significant part of the HIS, the Prescription Automatic Screening System (PASS) focuses on rational drug usage (e.g., drug interactions, pharmacologic antagonism, chemical incompatibility) and searches for available drug information, which could help in the avoidance of ADEs /ADRs caused by inappropriate drug usage [4].…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation